Dementia, discourse, difference and denial : "who did I become?" - J. Stirling (Law Text Culture, 1995)
If I am no longer a woman, why do I still feel I'm one? If no longer worth holding, why do I crave it? If no longer sensual, why do I still enjoy the soft texture of satin and silk against my skin? If no longer sensitive, why do moving song lyrics strike a responsive chord in me? My every molecule seems to scream out that I do, indeed, exist, and that existence must be valued by someone! Western medicine's fascination with the human brain and its workings is still marked by blurred boundaries between the mappings of neuro-anatomy and culturally inflected interpretations of neuro-psychology. This essay attempts to trace some of the intersections and overlaps between biomedical discourse and cultural politics as they come together in constructing the figure of the dementia body.